Integration of Complementary Medicine in Supportive Cancer Care: Survey of Healthcare Providers’ Perspectives - Suha Omran; Ziad Qadri; Ghada Shahrour (Jordan Journal of Nursing Research, 2023)
Background: Although complementary and traditional medicine (CTM) services are not widely available in Jordanian hospitals as part of oncology or palliative care, cancer patients have been found to be using CTM more frequently in recent years. A better understanding of healthcare providers’ perspectives and barriers to CTM use among cancer patients is an important step in integrating these therapies and procedures into mainstream cancer care. Objective: This study aims to explore healthcare providers’ perspectives and the barriers related to the integration of CTM among Jordanian cancer patients. Methods: A descriptive cross-sectional design was used to collect data from a sample of 240 healthcare providers (HCPs) using the Complementary and Traditional Medicine in Supportive Cancer Care Questionnaire. Results: Findings revealed that 49.6% of the participating HCPs considered that 50% of cancer patients had used CTM in the past year. Approximately 75% of participants considered improvement of well-being and QOL and reduction of chemotherapy side effects to be the greatest motives for CTM usage. Diet/nutrition therapy and herbs were perceived as the preferred CTM modalities during chemotherapy or advanced cancer. Conclusions: HCPs saw a need to improve communication between integrative physicians and cancer patients by focusing on the patient’s lifestyle and outlook, their well-being, and their ability to function. Participants perceived inadequate communication between CTM and conventional practitioners and oncologist skepticism and rejection of CTM as barriers to CTM integration. Implications to Nursing: CTM usage does involve some risks, so HCPs should be trained in why cancer patients choose to integrate CTM with conventional cancer treatments and how they can safely help them do so.